Marco temporal na jurisprudência indígena: uma análise do diálogo de cortes - Nogueira, Francisca Maria Benício Maia (2022)
This work presents a historical overview o f the conditions in which Brazilian indigenous people have lived in t h e country during crucial moments which attempt e d a g a i n s t t h e i r right s, s uch as the per iod of the P ombaline Directory and the Military Dictatorship. I also observe the period after the Fed eral Constitution of !988, during wh ich, while rights have been acquired, there have also been signi ficant setb acks. In this work , I, s pecifi cal ly, deal wi th the issue of the time frame thesis which was established on Petition 3,388 on the trial of the ind igeno us territory of Raposa Serra do Sol, in 2 009. Through a selection of the Federal Supreme Court decisions, I analyze the repe rcuss ion of the tim e frame thesis, in what regards the indigenous people’s rights. Furthermore, I observe if there has been a d ialog ue of courts, i.e., if the deci sions of the Federal Supreme Courts ha ve been in accordance with the Inter American Court of Huma n Rights as to the rig hts of in digenous people, mainly in what concerns the time frame thesis and the Indigenato theory.